2006
DOI: 10.1007/s00431-006-0237-6
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus and not age determines gastroenteritis severity in children: a hospital-based study

Abstract: These data provide the evidence that aetiology and not age determines diarrhoeal severity. The demonstration that diarrhoea was more severe in rotavirus-positive children supports the need for a rotavirus vaccine and for studies that address the duration of vaccine protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 33 publications
(25 reference statements)
6
33
1
9
Order By: Relevance
“…The most vulnerable of all the age groups were the children who are below the age of five years and it has been observed that the children [5 years of age have considerably increased RV infection rate in comparison with the adults (P \ 0.0001). Studies have reported that the most RV infections in children occurs before the age of 2 years [1,10,32,36] and in this study also the children \2 years of age demonstrated highest rate (50 %) of RV infections among all the patients belonging to different stages of life. EV infection was evenly distributed between the children (\5 years old) and adult ([5 years old) patient groups.…”
Section: Discussionsupporting
confidence: 66%
“…The most vulnerable of all the age groups were the children who are below the age of five years and it has been observed that the children [5 years of age have considerably increased RV infection rate in comparison with the adults (P \ 0.0001). Studies have reported that the most RV infections in children occurs before the age of 2 years [1,10,32,36] and in this study also the children \2 years of age demonstrated highest rate (50 %) of RV infections among all the patients belonging to different stages of life. EV infection was evenly distributed between the children (\5 years old) and adult ([5 years old) patient groups.…”
Section: Discussionsupporting
confidence: 66%
“…This is in agreement with a study carried out in Sudan (2010) which shows that children of illiterate parents are more infected with rotavirus [4]. This may reflect the relation of educational level of mother with hygiene as a risk factor for rotavirus infection [17].…”
Section: Pediatric Infectious Diseases: Open Access Issn 2573-0282supporting
confidence: 92%
“…Some studies found a relation between rotavirus diarrhea and male gender as a risk fact [16,17]. It was found that positive rotavirus result reported in children belong to young mothers with low education.…”
Section: Pediatric Infectious Diseases: Open Access Issn 2573-0282mentioning
confidence: 99%
“…Data about RV morbidity in Europe are available mainly for southern [2,9,26], northern [16,31], and western parts [1,3,6,11,28]. Only a few studies were performed in eastern Europe [22].…”
Section: Introductionmentioning
confidence: 99%